NEW DOSAGE FORM OF L-ARGININE BASED ON ITS COMPLEX WITH CELLULOSE ACETATE SULFATE AND ACTIVATED CARBON - Ekaterina Shakhno; Tatyana Savitskaya; Tatyana Pokrovskaya; Vladimir Yakushev; Dmitry Grinshpan (Belgorod National Research University, 2017)
Introduction: The oral route of L-arginine intake, despite its great comfort, is less effective in comparison with infusions. The development of new pharmaceutical forms for oral preparation is of undoubted interest. Objectives: To obtain a new dosage form of L-arginine by complexation with sodium salt of cellulose sulfate acetate (Na-CSA) followed by immobilization on activated carbon, and to evaluate its endothelial, cardioprotective and antihypertensive activity. Methods: UV-, visible spectroscopy, FTIR spectroscopy, viscometry, molecular mechanics, animal experiments with male Wistar albino rats in the modeling of L-NAME-induced endothelium dysfunction. Results: The physicochemical parameters of complexation, the adsorption activity of activated carbons of various origins with respect to individual L-arginine and its complex with Na-CSA were investigated. The greatest amount of adsorption and its smaller difference between L-arginine and the complex were taken into account when choosing activated carbon as a carrier (AUT-MI: GL-Arginine=320.2±0.1 mg/g, Gcomplex=340.2±0.1 mg/g; OU-A: GL-Arginine=210.1±0.1 mg/g, Gcomplex=235.1±0.1 mg/g; TH-90G: GL-Arginine=190.1±0.1 mg/g, Gcomplex=190.2±0.1 mg/g). Release of L-arginine as a result of its desorption into the model media of the human body was higher (96.3±0.5 wt.%) for the alkaline medium of intestines than for the acidic medium of stomach (10.0±0.1 wt.%). In animal experiments, it was shown that a combined preparation of L-arginine complex immobilized at doses of 30 mg/kg, 70 mg/kg and 200 mg/kg exhibits a pronounced antihypertensive, endothelioprotecive and cardioprotective activity at a dose of 200 mg/kg with L-NAME-induced nitric oxide deficiency (p